Management of syncope in the Emergency Department: a European prospective cohort study (SEED) - Reed, Matthew J; Karuranga, Suvi; Kearns, David; Alawiye, Salma; Clarke, Ben; Möckel, Martin; Karamercan, Mehmet; Janssens, Kelly; Riesgo, Luis Garcia-Castrillo; Torrecilla, Francisco Moya; Golea, Adela; Fernández Cejas, Juan Antonio; et al. (European journal of emergency medicine, 2024)
BACKGROUND AND IMPORTANCE: In 2018, the European Society of Cardiology (ESC) produced syncope guidelines that for the first-time incorporated Emergency Department (ED) management. However, very little is known about the characteristics and management of this patient group across Europe. OBJECTIVES: To examine the prevalence, clinical presentation, assessment, investigation (ECG and laboratory testing), management and ESC and Canadian Syncope Risk Score (CSRS) categories of adult European ED patients presenting with transient loss of consciousness (TLOC, undifferentiated or suspected syncope). DESIGN: Prospective, multicentre, observational cohort study. SETTINGS AND PARTICIPANTS: Adults (≥18 years) presenting to European EDs with TLOC, either undifferentiated or thought to be of syncopal origin. MAIN RESULTS: Between 00:01 Monday, September 12th to 23:59 Sunday 25 September 2022, 952 patients presenting to 41 EDs in 14 European countries were enrolled from 98 301 ED presentations (n = 40 sites). Mean age (SD) was 60.7 (21.7) years and 487 participants were male (51.2%). In total, 379 (39.8%) were admitted to hospital and 573 (60.2%) were discharged. 271 (28.5%) were admitted to an observation unit first with 143 (52.8%) of these being admitted from this. 717 (75.3%) participants were high-risk according to ESC guidelines (and not suitable for discharge from ED) and 235 (24.7%) were low risk. Admission rate increased with increasing ESC high-risk factors; 1 ESC high-risk factor; n = 259 (27.2%, admission rate=34.7%), 2; 189 (19.9%; 38.6%), 3; 106 (11.1%, 54.7%, 4; 62 (6.5%, 60.4%), 5; 48 (5.0%, 67.9%, 6+; 53 (5.6%, 67.9%). Furthermore, 660 (69.3%), 250 (26.3%), 34 (3.5%) and 8 (0.8%) participants had a low, medium, high, and very high CSRS respectively with respective admission rates of 31.4%, 56.0%, 76.5% and 75.0%. Admission rates (19.3-88.9%), use of an observation/decision unit (0-100%), and percentage high-risk (64.8-88.9%) varies widely between countries. CONCLUSION: This European prospective cohort study reported a 1% prevalence of syncope in the ED. 4 in 10 patients are admitted to hospital although there is wide variation between country in syncope management. Three-quarters of patients have ESC high-risk characteristics with admission percentage rising with increasing ESC high-risk factors.
Keywords: dospělí; synkopa; Prospective Studies; Humans; lidé středního věku; urgentní služby nemocnice; Middle Aged; prospektivní studie; Cohort Studies; Canada; mužské pohlaví; Adult; Emergency Service, Hospital; ženské pohlaví; Kanada; lidé; Syncope; kohortové studie; Male; Female